Effects of nusinersen on motor function in children with spinal muscular atrophy: a retrospective study - Chen, Yuyi; Yang, Dongling; Huang, Xuelin; Feng, Juntan; Zhao, Qingqing; Huang, Huixian; Liang, Lushi; Zhang, Xinxin; Ruan, Yiyan (Frontiers in Neurology, 2024)
Background: Spinal muscular atrophy (SMA) is a genetic progressive neuromuscular disease.Nusinersen is the first disease modifying drug approved to treat patients with SMA. Our study aimed to evaluate the efficacy of nusinersen treatment on motor function in children with SMA .A retrospective analysis was conducted on the data of 52 genetically confirmed SMA patients from November 2020 to September 2023. Motor function was assessed based on standardized scales from baseline to 14 months of follow-up.Of patients in this study, the majority had SMA type 2 (40/52, 76.9%), 5 (9.6%) and 7 (13.5%) patients had SMA types 1 and 3, respectively. The median disease duration was 11 months (range 0-52), and the median age at initiation of treatment was 44.5 months (range 5-192).Motor function of all the patients with SMA improved from baseline to 14 months of follow-up.Mean increases of 4.6-point (p=0.173), 4.7-point (p=0.021) and 2.7-point (p=0.013) were observed from baseline to 14 months of follow-up for the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders scores, the Hammersmith Functional Motor Scale Expanded (HFMSE) and the Revised Upper Limb Module (RULM), respectively. Increased disease duration and age of treatment initiation were negatively correlated with the changes in HFMSE scores (r=-0.567, p=0.043; r=-0.771 and p=0.002, respectively). Similar results were observed for the RULM scores (r=-0.714, p=0.014; r=-0.638 and p=0.035, respectively).Our study suggested that 14 months of treatment with nusinersen was effective and improved the motor function of children with SMA types 1, 2 or 3. In addition, disease duration and age at treatment initiation were negatively correlated with treatment outcome in the patients.